Implementasi Load Balancing Metode Per Connection Classifier (PCC) dan Failover menggunakan Mikrotik (Studi Kasus: STMIK PalComTech) - mahmud (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
In a company that relies on the internet as one of the main supports in running a company's business, it is necessary to have a computer network that is able to support this. The intended computer network must have good scalability and uptime. With the increasing number of ISPs (Internet Service Providers) currently available, this allows a company to have more than one internet source provider and also has a bandwidth that varies from each provider. By having more than one internet source, this can benefit companies in internet management, maintaining uptime and even costs. PCC load balancing aims to prevent overload that will later lead to slow or broken connections. By balancing the traffic load, it will reduce response time and increase throughput. Failover is a technique to move a broken connection to an available connection. In this study, load balancing will be carried out on 2 different ISPs, each of which has a different bandwidth of 50 Mbps and 100 Mbps, and has several routing policies to determine the main and secondary routing in the application of failover.